Social Responsibility And Teamwork In The Investigative Skills Of Teachers In Covid-19 Pandemic At The Isaíasardiles Educational Institution, Pachacamac 2020. - et. al., Carmen Edith Miranda Olivos, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study aimed to determine the incidence of social responsibility and teamwork on the investigative skills of teachers, and responds to the institutional educational problem. With a quantitative approach, explanatory type and causal correlational design, with a sample comprised of 77 teachers from the IsaíasArdiles Educational Institution of Pachacamac; Questionnaires were used for the variables, the general objective of the research was: To determine the incidence of social responsibility and teamwork in the investigative skills of the IsaíasArdiles Educational Institution, Pachacamac, 2020; and the specific objectives were: Determine the incidence of social responsibility and teamwork in the ability to problematize the educational reality of the IsaíasArdiles Educational Institution, Pachacamac, 2020; determine the incidence of social responsibility and teamwork in the ability to theorize the educational reality of the IsaíasArdiles Educational Institution, Pachacamac, 2020; and determine the incidence of social responsibility and teamwork in the ability to verify the educational reality of the IsaíasArdiles Educational Institution, Pachacamac, 2020; and in the hypothesis test the linear regression statistic was used; and after data collection, the following conclusion was reached: Social responsibility and teamwork significantly affect the investigative skills of the IsaíasArdiles Educational Institution, Pachacamac, 2020; having obtained a value p = 0.000 in the linear regression test.